2011
DOI: 10.1128/aem.00033-11
|View full text |Cite
|
Sign up to set email alerts
|

Association of Earthworm-Denitrifier Interactions with Increased Emission of Nitrous Oxide from Soil Mesocosms Amended with Crop Residue

Abstract: Earthworm activity is known to increase emissions of nitrous oxide (N 2 O) from arable soils. Earthworm gut, casts, and burrows have exhibited higher denitrification activities than the bulk soil, implicating priming of denitrifying organisms as a possible mechanism for this effect. Furthermore, the earthworm feeding strategy may drive N 2 O emissions, as it determines access to fresh organic matter for denitrification. Here, we determined whether interactions between earthworm feeding strategy and the soil de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 47 publications
3
18
0
2
Order By: Relevance
“…The only soil faunal group so‐far acknowledged to have a pronounced influence on soil‐derived N 2 O emissions are earthworms (Lubbers, Van Groenigen, et al, ). These macro‐detritivores have been well studied with respect to N 2 O emissions and they can increase N 2 O emissions considerably through interacting with the microbial community (Drake & Horn, ; Nebert, Bloem, Lubbers, & Groenigen, ), by increasing the mineralization of nutrients and altering the soil structure (Lubbers, Brussaard, Otten, & Groenigen, ; Lubbers, Van Groenigen, et al, ). Other macrofauna, such as isopods and grubs, and mesofaunal groups, such as potworms, fungivorous mites and springtails, can also influence N 2 O emissions (Kuiper et al, ; Majeed et al, ; Tianxiang, Huixin, Tong, & Feng, ; Van Vliet, Beare, Coleman, & Hendrix, ).…”
Section: Introductionmentioning
confidence: 99%
“…The only soil faunal group so‐far acknowledged to have a pronounced influence on soil‐derived N 2 O emissions are earthworms (Lubbers, Van Groenigen, et al, ). These macro‐detritivores have been well studied with respect to N 2 O emissions and they can increase N 2 O emissions considerably through interacting with the microbial community (Drake & Horn, ; Nebert, Bloem, Lubbers, & Groenigen, ), by increasing the mineralization of nutrients and altering the soil structure (Lubbers, Brussaard, Otten, & Groenigen, ; Lubbers, Van Groenigen, et al, ). Other macrofauna, such as isopods and grubs, and mesofaunal groups, such as potworms, fungivorous mites and springtails, can also influence N 2 O emissions (Kuiper et al, ; Majeed et al, ; Tianxiang, Huixin, Tong, & Feng, ; Van Vliet, Beare, Coleman, & Hendrix, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, E. fetida enhanced 4.2-fold times N 2 O emissions from soil. It was found that L. rubellus increased cumulative N 2 O emissions by 76 % (Nebert et al 2011). Also, the presence of Aporrectodea turgida and Lumbricus terrestris increased the amount N 2 O produced in soil (Chen et al 2014).…”
Section: Discussionmentioning
confidence: 94%
“…The earthworm-induced N 2 O accounted for the majority of the cumulative N 2 O emission in our mesocosms (Table 1). Nebert et al (2011) reported that L. rubellus increased cumulative N 2 O emissions by affecting activity of denitrifiers through influencing substrates supply. Therefore, we concluded that N 2 O emissions from mesocosms with earthworms (E. fetida) were mitigated by NI application.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis on the effect of earthworms on soil greenhouse gas emissions reported an average earthworm-induced increase in N 2 O emissions of 42 % (Lubbers et al, 2013). This was hypothesized to be the result of effects on the denitrifier community as well as changes in soil structure affecting gas diffusivity and anaerobicity Horn, 2006, 2007;Nebert et al, 2011). Further work on soil microbiology and soil structure is needed to determine what are the exact effects of earthworm activity on microbial producers and consumers of N 2 O and on net soil N 2 O emission.…”
Section: Soil 1 235-256 2015mentioning
confidence: 99%